Immigration Reform in the United States:IRCA Revived: Contextualizing the Border Security, Economic Opportunity and Modernization Act (S. 744) - Popat, Naila (Université d'Ottawa | University of Ottawa, 2014)
The Immigration Reform and Control Act (IRCA) 1986, was the last comprehensive piece of immigration legislation passed in the United States and it failed to meet the needs of employers, protect immigrants and create equitable access in U.S. immigration. With the Border Security, Economic Opportunity and Modernization Act (S. 744) passed in the U.S. Senate, it might be possible that a comprehensive bill better suited to the needs of the American economy and people will replace the IRCA. However, due to the political nature of immigration reform in the U.S., S. 744 contains compromises that disproportionately affect communities living along the border without providing the financial resources to regulate the implementation of S. 744. Although the IRCA failed to meet expectations, namely achieving a lasting reduction in undocumented migration, the authors of S. 744 have chosen to use the IRCA as the framework to structure the new bill. S. 744 will focus on giving employers greater access to temporary foreign workers, allow undocumented immigrants the ability to transition to permanent resident status and secure U.S. and Mexico border by completing the 2,000-mile security fence. The success of S. 744 rests on its final stated goal of securing the border. Without a 90% apprehension rate, not a single undocumented immigrant will be able to apply for legalization under the new law. Undocumented immigrants will continue to “live in the shadows”, employers will not be subject to greater sanctions, regulatory bodies will lack funds to protect undocumented workers, and border communities will become home to the largest border patrol in the world. (Bean, Brown, 2012 & Cushing, 2013) Employing a less unidirectional approach giving greater importance to the rights of undocumented immigrants in relation to securing the border could increase the possibility of undocumented immigrants having access to legalization programs as a result of the unrealistic conditions of a “secure” border as described in the legislation. Finally, recognizing that the needs of one community do not outweigh those of another, supporters of S. 744 in their single minded push for immigration reform overlook the needs of communities living along the border, while those who oppose S. 744 argue that any bill with a legalization program rewards individuals in violation of U.S. law having entered the United States without authorization. This paper will look at the conflicting arguments and interests to offer an understanding of how effective S. 744 may potentially be in repairing the U.S. immigration system, should it be signed into law.